Sejarah Peradaban Islam Sebagai Ilmu Pengetahuan - M. Nasron; Ardianti Yunita Putri; Elia Mariza (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2023)
The purpose of this writer is to know the history of Islamic civilization as a science. This writer uses library research (library research). History prioritizes the orientation of understanding or interpretation of historical facts. The findings from this study are that in the development of science in modern times, science is becoming more interconnected with one another. This is referred to as the integration of the interconnection of science in Islam, where the Qur'an is the center of integration, and then the Hadith.